Optimizing Aminoglycoside Therapy for Nosocomial Pneumonia Caused by Gram-Negative Bacteria - Kashuba, Angela D. M. (American Society for Microbiology, 1999)
Nosocomial pneumonia is a notable cause of morbidity and mortality and leads to increases in lengths of hospital stays and institutional expenditures. Aminoglycosides are used to treat patients with these infections, but few data on the doses and schedules required to achieve optimal therapeutic outcomes exist. We analyzed aminoglycoside treatment data for 78 patients with nosocomial pneumonia to determine if optimization of aminoglycoside pharmacodynamic parameters results in a more rapid therapeutic response (defined by outcome and days to leukocyte count resolution and temperature resolution). Cox proportional hazards, Classification and Regression Tree (CART), and logistic regression analyses were applied to the data. By all analyses, the first measured maximum concentration of drug in serum (C(max))/MIC predicted days to temperature resolution and the second measured C(max)/MIC predicted days to leukocyte count resolution. For days to temperature resolution and leukocyte count resolution, CART analyses produced breakpoints, with an 89% success rate at 7 days of therapy for a C(max)/MIC of >4.7 and an 86% success rate at 7 days of therapy for a C(max)/MIC of >4.5, respectively. Logistic regression analyses predicted a 90% probability of temperature resolution and leukocyte count resolution by day 7 if a C(max)/MIC of ≥10 is achieved within the first 48 h of aminoglycoside therapy. Aggressive aminoglycoside dosing immediately followed by individualized pharmacokinetic monitoring would ensure that C(max)/MIC targets are achieved early in therapy. This would increase the probability of a rapid therapeutic response for pneumonia caused by gram-negative bacteria and potentially decreasing durations of parenteral antibiotic therapy, lengths of hospitalization, and institutional expenditures, a situation in which both the patient and the institution benefit.